2022
DOI: 10.3390/microorganisms10071450
|View full text |Cite
|
Sign up to set email alerts
|

Viral Vector Vaccine Development and Application during the COVID-19 Pandemic

Abstract: With the accumulation of mutations in SARS-CoV-2 and the continuous emergence of new variants, the importance of developing safer and effective vaccines has become more prominent in combating the COVID-19 pandemic. Both traditional and genetically engineered vaccines have contributed to the prevention and control of the pandemic. However, in recent years, the trend of vaccination research has gradually transitioned from traditional to genetically engineered vaccines, with the development of viral vector vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 71 publications
0
38
0
1
Order By: Relevance
“…VVVs can induce long-lasting and strong cellular responses to eliminate virus-infected cells. Cytotoxic CD8 + T cells rapidly proliferate and differentiate in response to antigens, while cell-mediated immunity induces natural killer cells and macrophages to eliminate intracellular pathogens (58). On the other hand, most of the VVVs can induce powerful humoral immunity, however it has been observed that immunogen design can affect VVV-mediated humoral immunogenicity (58).…”
Section: Viral Vector Vaccines (Vvvs)mentioning
confidence: 99%
“…VVVs can induce long-lasting and strong cellular responses to eliminate virus-infected cells. Cytotoxic CD8 + T cells rapidly proliferate and differentiate in response to antigens, while cell-mediated immunity induces natural killer cells and macrophages to eliminate intracellular pathogens (58). On the other hand, most of the VVVs can induce powerful humoral immunity, however it has been observed that immunogen design can affect VVV-mediated humoral immunogenicity (58).…”
Section: Viral Vector Vaccines (Vvvs)mentioning
confidence: 99%
“…Furthermore, adenovirus is so common to humans that most humans have developed preexisting immunity to adenoviral vectors, reducing their efficacy in gene expression. 47,48 Furthermore, the scalability of viral vectors at a commercial scale remains as another challenge. The most common method of producing viral vectors is transfection of human embryonic kidney (HEK)293 cells with plasmids for viral components.…”
Section: Viral Vectorsmentioning
confidence: 99%
“… 4 - Safely produced without having to handle viral particles or cell cultures and animal matrix 37 - Unstable and requires ultra-cold storage facility 29 , 39 41 24% VV - Stronger immune response. Elicit robust humoral and cellular responses with a single dose by mimicking natural infection, providing long-term immune response 40 , 41 - Pre-existing immunity against human viral vectors can attenuate immune responses 42 , 43 - Potential risk for infection and inflammation that can cause adverse reactions 44 , 45 - Risk of genomic integration 31 - Optimization of the cellular system is required for efficient viral vector 31 - Safely produced without having to handle viral particle 29 - Can be easily produced on large scale 46 - Stable and do not require stringent storage conditions 41 21 (VVnr) 4 (VVr) 2 (VVr +APC) 1 (VVnr + APC) 16% IV - Weaker immune response compared to live attenuated vaccines, requiring a higher dose, booster dosages, or adjuvants 29 , 47 , 48 - Induction of long-lived humoral and cellular immune responses with several booster doses (results of nonrandomized trial among health care workers administered with BBIBP-CorV) 49 - Less risk of virulence reversion compared with live attenuated virus vaccine if properly inactivated, which is also suitable for immunocompromised patients 29 - Potential induction of vaccine-induced eosinophilic pulmonary response 50 - Require high levels of live pathogens for production 51 - Inactivation process can affect the immunogenicity of the antigen due to structural deformation 29 , 31 - Ease of transport and storage. Inactivated virus vaccine can be stored at 2–8 °C, enabling storage in countries with limited cold storage facilities 48 22 13% DNA …”
Section: Currently Available Covid-19 Vaccine Platformsmentioning
confidence: 99%
“…By contrast, intramuscular or intradermal administration of vaccines mainly induces IgG without inducing the secretory IgA 22 . Considering that the SARS-CoV-2 Omicron variant (B1.1.529) preferentially infects and replicates in the upper respiratory airways, inducing high levels of neutralizing antibodies in the nasal mucosa is vital for the prevention of viral transmission 41 , 69 . The neutralizing potency of secretory IgA in the nasopharynx is 7.5-fold higher than that of IgG in serum 70 .…”
Section: Currently Available Covid-19 Vaccine Platformsmentioning
confidence: 99%